AGAMA, MEDIA, DAN KEKUASAAN: ANALISIS ISU AGAMA DALAM PILPRES RI 2014 - Hasan, Amirul (LP2M IAIN Mataram, 2014)
In 2014, Indonesia conducted the fourth Indonesian president election. This contestation not only engaging power issue as the goal, media as the instrument, but also the strengthening of theology of religion issue. After carrying out a research with qualitative approach and library research method, the researcher concluded that media had significant role either to deliver the information about Indonesian president election process or to deliver some issues which had deliberately generated on behalf of certain parties. The existence of media has replaced the function of political party in persuading and influencing the voters. Embodied in media, religion and its generated symbols became sources of legitimation to retake or to defend the status quo by most of political elites. Thus religion had become effective political resources to the elites or political actors to gain electoral support or obtaining votes in such contestation and succession. Religion otherwise has been able to be a decisive tools to delegitimize power of an ongoing regime.